Assistência obstétrica sob a ótica de mulheres atendidas no Sistema Único de Saúde em Goiânia, Goiás - SANTOS, Heliane Fernandes Lourenço (2011)
INTRODUCTION: The policy of humanization of prenatal care, labor and delivery within the Health System recommends actions that should guarantee women the benefits of scientific advances, and ultimately, allow and encourage the practice of female citizenship, rescuing empower women in the process parturitivo, ensuring privacy, easy access to consultations and examinations, information and procedures proven beneficial. Avoiding unnecessary interventions, sharing with the mother decisions on measures to be adopted and establishing relationships based on ethical, social and professional (MINISTRY OF HEALTH, 2006). The study aims to analyze the adoption of standards of humane care to prenatal care, labor and birth, from the perspective of women served by the Health System in Goiânia, Goiás METHODOLOGY: A descriptive and exploratory qualitative approach. Data collection took place from May to July 2010 in Goiânia, Goiás For data collection we used semi-structured interview. RESULTS: The profile of the subjects were 21 pregnant women aged 18-31 years, most had high school, lived in a stable income and a minimum wage. Were prepared two thematic categories: Pre-natal care and childbirth and birth. It was found that prenatal was easy access to exams and the Family Health Strategy. However the Centers for Integral Health was difficult to access appointments. It found no or little information about the process parturitivo prevailed and the will or medical decision in choosing the type of delivery. During labor and delivery practices walking, freedom of position, power and right to analgesia were less evident, the right of the accompanying family is still not respected. Breastfeeding was encouraged after birth, rooming-in was seen as a place of abandonment and loneliness. The perception of the mother and birth care in the public health data direct to lack of education of health professionals. CONCLUSION: The data pointed to situations such as difficult access to prenatal care, lack of conduct and procedures to be adopted, absence of women's participation in decision making and lack of support in childbirth, situations that contradict with the policy advocated by humanizing prenatal care, labor and birth.